Eksperimentasi Strategi Baca Tulis al-Qur'an Terhadap Peningkatan Kemampuan Menghafal Siswa Ditinjau dari Perhatian Orang Tua - Anam, Saeful; Rohmah, Nur Kholifatur (Academia Publication, 2022)
This study aims to test how much influence parental attention has on the ability to memorize the Qur'an of students at SMK Ar-Rahma Mandiri Indonesia Pasuruan. In addition, this study aims to identify and create new media, and is expected to provide input and evaluation for the learning process of the Qur'an both in schools and other Qur'anic institutions. And add a new discourse to be able to develop the scientific repertoire of Islam. This research is a type of experiment research with a quantitative approach with true experimental design research. The results obtained by the researcher that there is a significant difference in the level of influence of parental attention and BTQ strategy on the memorization ability of the students of SMK Ar-Rahma Mandiri Indonesia Pasuruan with a value of Sig. (2-tailed) < 0.05, i.e. 0.002 < 0.05, which means that there is a significant difference between the level of influence of parental attention and the BTQ strategy on the memorization ability of the students of SMK Ar-Rahma Mandiri Indonesia Pasuruan. And the magnitude of the effect based on the R Squared value of 0.739 lies at (0.71 0.90) with a